Analysis of Infrastructure Spending, Construction Cost Index, Population Density on Road Stability - Zuhro, Siti Sarah; Yuliawan, Dedy; Andrian, Thomas (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study investigates the impact of infrastructure spending, the Construction Cost Index (CCI), and population density on the stability of provincial roads in Indonesia from 2017 to 2022, covering periods before and during the COVID-19 pandemic. Using a panel data regression analysis across 28 provinces, the research found that population density and the COVID-19 pandemic had significant positive effects on road stability, while infrastructure spending and CCI showed no statistically significant impact. The results highlight the crucial role of population dynamics and the pandemic in shaping road conditions, while questioning the effectiveness of infrastructure spending and CCI in enhancing road stability. The study underscores the need for more targeted policies that consider demographic factors and external shocks like pandemics in maintaining and improving road infrastructure. These findings provide valuable insights for policymakers in formulating infrastructure strategies and contribute to the broader discourse on public infrastructure management in Indonesia.